2014
DOI: 10.4067/s0717-97072014000300021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Quorum Sensing by Drimane Lactones From Chilean Flora

Abstract: Fifteen native Chilean plants were evaluated against the quorum sensing (QS) biosensor AI-1, Chromobacterium violaceum ATCC 12472. Three extracts showed inhibitory activity of QS: Drymis winteri J.R, Psoralea glandulosa L and Peumus boldus. Purification of secondary metabolites from barks of Drimys winteri showed that drimane sesquiterpenes were the main compounds in the tree. Polygodial, drimenol, isodrimeninol, drimenin, isodrimenin, cinnamolide and valdiviolide were isolated and evaluated in QS inhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…It is present at all social and religious meetings, called “guillatún” and “machitún”, where the healer, or “machi”, uses Canelo leaves or sap as medicine. Among the three products of focus here, drimane sesquiterpenoids stand out as secondary metabolites withpotent fungicidal, anti-feeding and insecticidal activities, and drimane sesquiterpene lactones have demonstrated activity on bacterial quorum sensing [ 17 , 18 ]. P. Mitiqui (Lindl) (Asteraceae, Compositae) is another endemic plant of the Central Zone of Chile.…”
Section: Introductionmentioning
confidence: 99%
“…It is present at all social and religious meetings, called “guillatún” and “machitún”, where the healer, or “machi”, uses Canelo leaves or sap as medicine. Among the three products of focus here, drimane sesquiterpenoids stand out as secondary metabolites withpotent fungicidal, anti-feeding and insecticidal activities, and drimane sesquiterpene lactones have demonstrated activity on bacterial quorum sensing [ 17 , 18 ]. P. Mitiqui (Lindl) (Asteraceae, Compositae) is another endemic plant of the Central Zone of Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Also, polygodial (01-100 µM) inhibited the rhythmic spontaneous contractions of the rat portal vein (Emax by 75 ± 2%.) These results strongly suggest that the vasorelaxant actions produced by polygodial in rat portal vein are associated with inhibition of calcium influx through voltage-sensitive channels and interaction with protein kinase Cdependent mechanisms (Cárcamo et al, 2014).…”
Section: Cardiovascular Effectsmentioning
confidence: 70%
“…Cinnamolide and valdiviolide are αβ unsaturated lactones with the carbonyl in position 12 of the drimane skeleton, whereas drimenin, isodrimenin and isodrimeninol have the carbonyl group at position 11 and are not active. This relationship between structure and activity shows the high specificity of the QS system (Cárcamo et al, 2014).…”
Section: Quorum-sensing Inhibitionmentioning
confidence: 85%
“…The 1 H NMR (Table S1, Supporting Information) and 13 C NMR (Table S2, Supporting Information) results are in excellent agreement with previous data. 11 ,12 The chemical characterization of drimane sesquiterpenoids coincides with that obtained by X-ray studies, 13−15 where a basic structural framework is shown: a trans-decalin moiety with a Δ 7 (8) double bond, giving a twisted chair conformation at the second ring and conferring a planar C-7−C-8−C-12 dihedral angle of 126.7°for dendocarbin A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%